A Study on effectiveness photographic images of the Perak State Tourism Campaign Billboards / Khairul Anuar Ibrahim, Md Nagib Padil and Mohd Nuri Yaacob - Khairul Anuar, Ibrahim; Md Nagib, Padil; Mohd Nuri, Yaacob (Universiti Teknologi MARA, Perak, 2018)
The objective of this research is to study the effectiveness of photographic images used on tourism campaign billboard in Perak. It will also gauge the extent of respondent’s perception and understanding on the important of photographic images on the tourism billboard in Perak. In order to ensure the success and effectiveness of the method, one study has to be conducted to obtain feedback from the public regarding the images which are featured on the tourism advertisement billboards. It is hoped that findings from this research would be able to gain respondents’ feedback in providing information to the researcher so that the effectiveness of photographic images used as one of the mediums on Perak’s tourism advertisement billboards can be identified. Results from this study would serve as guidance to the relevant authority by producing suggestions of new and high quality photographic images on the tourism advertisement billboards in Perak